Pengaruh Loan to Deposit Ratio, Non Performing Loan, dan Net Interest Margin terhadap Return on Assets PT Bank Pembangunan Daerah di Indonesia Tahun 2024 - Arum Sekarwati; Puji Astuti; Badrus Zaman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study examines the decline in profitability of Regional Development Banks (RDBs) in Indonesia during 2024, as reflected by the decrease in Return on Assets (ROA). Based on Indonesian Banking Statistics, ROA declined compared to 2023 and showed a quarterly decrease from the first to the second quarter before remaining relatively stable through the fourth quarter despite increased profits. This study aims to analyze the effects of the Loan to Deposit Ratio (LDR), Non-Performing Loan (NPL), and Net Interest Margin (NIM) on ROA. A quantitative approach with a causal associative method was employed using secondary data from the quarterly financial statements of 27 RDBs selected through purposive sampling. Data were analyzed using multiple linear regression with SPSS version 25. The results indicate that LDR has no significant effect on ROA, while NPL has a significant negative effect and NIM has a significant positive effect on ROA. Simultaneously, LDR, NPL, and NIM significantly influence ROA, with NIM identified as the most dominant determinant of profitability. The findings provide practical implications for RDB management to improve profitability by maintaining credit quality and optimizing productive asset management.